Delta State of Nigeria estimates 2006 - Delta State (Nigeria); Delta State (Nigeria). ([Asaba, Nigeria] : Ministry of Economic Planning, 2006)
This is the 2006 budget of Delta State of Nigeria delivered to the House of Assembly by the Governor of Delta State, His Exc. Chief James Ibori on Tuesday, November 22, 2005.
oif 03/10/2019
Nigeriana
Keywords: Budget; Expenditures, Public; Delta State (Nigeria); Nigeria